Clever : leading your smartest, most creative people - Goffee, Robert. (Harvard Business Press, 2009)
Leading clever people can be enormously challenging, yet doing so effectively is the key to your organization's sustained success. Lively and engaging, this book provides the ideas, practices, and examples you need to create an environment where your most brilliant people can flourish.